Multicomponent analysis of the tumour microenvironment reveals low CD8 T cell number, low stromal caveolin-1 and high tenascin-C and their combination as significant prognostic markers in non-small cell lung cancer - Onion, David; Isherwood, Mark; Shridhar, Naveen; Xenophontos, Mikalena; Craze, Madeleine L.; Day, Laura J.; Gárcia-Marquez, Maria A.; Pineda, Robert G.; Reece-Smith, Alex M.; Saunders, John H.; Duffy, John P.; Argent, Richard H.; et al. (Impact Journals, 2017)
The complex interplay of the tumour microenvironment (TME) and its role in disease progression and response to therapy is poorly understood. The majority of studies to date focus on individual components or molecules within the TME and so lack the power correlative analysis. Here we have performed a multi-parameter analysis of the TME in 62 resectable non-small cell lung cancer (NSCLC) specimens detailing number and location of immune infiltrate, assessing markers of cancer-associated fibroblasts, caveolin-1 and tenascin-C, and correlating with clinicopathological details, as well as markers of disease progression such as epithelial-to-mesenchymal transition (EMT). The influence of individual parameters on overall survival was determined in univariate and multivariate analysis and the combination of risk factors and interplay between components analysed. Low numbers of CD8 T cells, low stromal levels of caveolin-1 or high levels of tenascin-C were significant prognostic markers of decreased overall survival in both univariate and multivariate analysis. Patients with two or more risk factors had dramatically reduced overall survival and those with all three a median survival of just 7.5 months. In addition, low levels of tumour E-cadherin correlated with reduced immune infiltrate into the tumour nests, possibly linking EMT to the avoidance of CD8 T cell control. The multicomponent approach has allowed identification of the dominant influences on overall survival, and exploration of the interplay between different components of the TME in NSCLC.